Isokinetic trunk muscular strength of female judo athletes: Characteristics of lightweight, middleweight and heavyweight class athletes evaluated from decreases in peak torque according to increases in angle velocity - Nakata, N.; Kuwamori, M.; Masuchi, K.; Kanamaru, Y.; Takezawa, T.; Fukumi, T.; Kasugai, A. (Research Journal of Budo, 2017)
Previous studies have suggested that trunk muscular strength is an important factor for the competitive ability of female judo athletes. The purpose of this study was to clarify the characteristics of lightweight, middleweight, and heavyweight class athletes with decreases in peak torque according to increases in angle velocity. The subjects were 61 female judo athletes consisting of 28 lightweight, 17 middleweight, and 16 heavyweight class athletes without lower back pain. We used the CYBEX 770-Norm System with a Trunk Extension / Flexion Unit to measure peak torque during trunk extension and flexion. The peak torque was measured at angle velocities of 30, 60, 90, 120, and 150 deg/s, according to the CYBEX TEF standard protocol.